$q$-Hook formula of Gansner type for a generalized Young diagram - Kento Nakada (Discrete Mathematics & Theoretical Computer Science, 2009)
The purpose of this paper is to present the $q$-hook formula of Gansner type for a generalized Young diagram in the sense of D. Peterson and R. A. Proctor. This gives a far-reaching generalization of a hook length formula due to J. S. Frame, G. de B. Robinson, and R. M. Thrall. Furthurmore, we give a generalization of P. MacMahon's identity as an application of the $q$-hook formula.